2018
DOI: 10.1029/2018jb015748
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Gas Flow and Hydrate Formation Within the Hydrate Stability Zone

Abstract: We form methane hydrate by injecting methane gas into a brine‐saturated, coarse‐grained sample under hydrate‐stable thermodynamic conditions. Hydrate forms to a saturation of 11%, which is much lower than that predicted assuming three‐phase (gas‐hydrate‐brine) thermodynamic equilibrium (67%). During hydrate formation, there are temporary flow blockages. We interpret that a hydrate skin forms a physical barrier at the gas‐brine interface. The skin fails periodically when the pressure differential exceeds the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 72 publications
(104 reference statements)
5
49
0
Order By: Relevance
“…This model was conceptually described by Ginsburg () and Soloviev and Ginsburg () and is similar to the hydrate shell theory used to describe the interactions between gas and water in bubble systems (Rehder et al, ). Meyer et al () and Sahoo et al () demonstrated the presence of hydrate shells and the diffusion‐limited hydrate formation with laboratory‐controlled experiments in porous media. This model is also very similar to the coupled thermodynamic simulations of Fu et al ().…”
Section: Models Of Methane Hydrate Formation In Geological Systemsmentioning
confidence: 99%
“…This model was conceptually described by Ginsburg () and Soloviev and Ginsburg () and is similar to the hydrate shell theory used to describe the interactions between gas and water in bubble systems (Rehder et al, ). Meyer et al () and Sahoo et al () demonstrated the presence of hydrate shells and the diffusion‐limited hydrate formation with laboratory‐controlled experiments in porous media. This model is also very similar to the coupled thermodynamic simulations of Fu et al ().…”
Section: Models Of Methane Hydrate Formation In Geological Systemsmentioning
confidence: 99%
“…The role of a vapor phase in the nucleation and accumulation of gas hydrate in porous media is the focus of several laboratory studies in the Special Section as well (Meyer, Flemings, & DiCarlo, , Meyer, Flemings, DiCarlo, You, et al, ; Sahoo et al, ). Both Meyer, Flemings, DiCarlo, You, et al () and Sahoo et al () describe experiments in which gas hydrate does not form to saturations as high as are predicted based on thermodynamic equilibrium for the three phase system (gas‐pore fluid‐gas hydrate).…”
Section: Special Section Themesmentioning
confidence: 99%
“…The role of a vapor phase in the nucleation and accumulation of gas hydrate in porous media is the focus of several laboratory studies in the Special Section as well (Meyer, Flemings, & DiCarlo, , Meyer, Flemings, DiCarlo, You, et al, ; Sahoo et al, ). Both Meyer, Flemings, DiCarlo, You, et al () and Sahoo et al () describe experiments in which gas hydrate does not form to saturations as high as are predicted based on thermodynamic equilibrium for the three phase system (gas‐pore fluid‐gas hydrate). Meyer, Flemings, DiCarlo, You, et al () start with methane migrating through the sediment sample already held within the P‐T conditions for hydrate stability, whereas Sahoo et al () inject methane gas and then allow the system to equilibrate before lowering the temperature, following a method first described by (Waite et al, ).…”
Section: Special Section Themesmentioning
confidence: 99%
See 2 more Smart Citations